2016
DOI: 10.1111/ctr.12864
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of cardiac morphology and function following kidney transplantation

Abstract: Background Abnormal cardiac morphology is a risk factor for cardiovascular complications in kidney transplant patients. A supraphysiologic level of fibroblast growth factor 23 (FGF-23) has been associated with myocardial hypertrophy in this patient population. Our aim was to evaluate the change in cardiac morphology and function following kidney transplantation and to evaluate the association between the change in FGF-23 concentrations and cardiac morphology. Methods We performed a longitudinal, prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
4
3
0
1
Order By: Relevance
“…Previous cardiovascular magnetic resonance-based studies, evaluating the relationship between normo-to microalbuminuria and LV mass in non-CKD populations, were performed solely in hypertensive individuals [9,10], limiting conclusions on whether found associations were independent of blood pressure. Our findings are supported by the improved cardiac function and decrease in LV mass index after renal transplantation [22,23]. Moreover, elevated circulating levels of endothelial glycocalyx degrading enzyms, such as syndecan-1 and thrombomodulin, have shown to normalize after kidney transplantation, indicating an improved systemic endothelial function [24].…”
Section: Discussionsupporting
confidence: 75%
“…Previous cardiovascular magnetic resonance-based studies, evaluating the relationship between normo-to microalbuminuria and LV mass in non-CKD populations, were performed solely in hypertensive individuals [9,10], limiting conclusions on whether found associations were independent of blood pressure. Our findings are supported by the improved cardiac function and decrease in LV mass index after renal transplantation [22,23]. Moreover, elevated circulating levels of endothelial glycocalyx degrading enzyms, such as syndecan-1 and thrombomodulin, have shown to normalize after kidney transplantation, indicating an improved systemic endothelial function [24].…”
Section: Discussionsupporting
confidence: 75%
“…This finding resonated with other studies that discerned evidence of a reduced risk for stroke after KT [23]. With respect to the pathogenesis of vascular function after KT, studies from Kensinger et al reported a significant association between decreased fibroblast growth factor 23 levels and improved left ventricular mass index following transplantation, and that the improved endothelial function after transplantation was maintained for up to two years [29,30]. KT also ameliorated dyslipidemia, which is a well-recognized cardiovascular disease risk factor characterized by a decreased concentration of high-density lipoprotein and an increased concentration of triglycerides that is associated with kidney impairment [31].…”
Section: Discussionsupporting
confidence: 75%
“…The cohort of KTRs suffers from many cardiovascular complications. Echocardiographic abnormalities, as well as concentric hypertrophy and concentric remodeling [23], are common findings, resulting in left ventricular dysfunction [24]. Although no major differences in the prevalence of self-reported complaints have been found between the analyzed patient groups in our study, the use of LVD-36 questionnaire allowed to uncover more discrete discrepancies regarding EC in this patient cohort.…”
Section: Discussionmentioning
confidence: 52%